Health-promoting leadership in education: Relevance to teachers in township schools - Kwatubana, Siphokazi (Frontiers in Education, 2022)
Teachers in township schools are vulnerable because of the low socio-economic conditions of the communities in which their schools are located. Such factors coupled with personal challenges can have a negative impact on their health. The aim of this research was to investigate the value of health-promoting leadership (HPL) in township schools. A qualitative approach was followed to gather information about the latter. Data were gathered by means of diary keeping, recording and individual interviews. Sixteen participants participated in the research and were engaged in the research for four months. A total of 32 interviews were conducted; each participant was interviewed twice. The findings revealed that HPL was perceived as relevant to the participating schools as it enhanced healthy working conditions, such as a health-promoting culture, health awareness and close working relationships (community). It is recommended that more attention be given to HPL, focusing on physical environments and safety and providing social support and health awareness programs to enhance teachers’ physical and mental health.